A Descriptive Study Of Characteristics, Interests And Career Objectives Of Agricultural Communications Students - Mark Tucker; Curtis Paulson (Journal of Applied Communications, 1988)
To build efficient curricula that will attract and retain students, agricultural communications faculty and administrators must identify students' needs and interests. Although previous research has documented characteristics of agricultural communications curricula and views of agricultural communications professionals, there has been little published information about characteristics or views of agricultural communications students themselves. We surveyed 66 agricultural communications students at Texas Tech University to generate information on student characteristics, interests, and career objectives. Findings indicate that such students have high levels of interest in both agricultural and mass communications subjects. However, these students are more likely to prefer agricultural classes, internships, and club affiliations over those offered in mainstream communications. If the agricultural communications option were not available, more than half of the students would find another major in the College of Agricultural Sciences. This and other information will help us build the agricultural communications curriculum and know more about our students.